2021
DOI: 10.1186/s13018-021-02543-x
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA CASC19 accelerates chondrocytes apoptosis and proinflammatory cytokine production to exacerbate osteoarthritis development through regulating the miR-152-3p/DDX6 axis

Abstract: Background Osteoarthritis (OA) is one kind of degenerative joint disease that happens in articular cartilage and other joint tissues. Long non-coding RNAs (lncRNAs) have been reported to serve as pivotal regulators in many diseases, including OA. However, the role and relevant regulatory mechanisms of CASC19 in OA remain unknown. Methods The expression levels of CASC19, miR-152-3p, and DDX6 were identified by reverse-transcription polymerase chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…miR-152 attenuated lncRNA PVT1induced apoptosis via c-MET/PI3K/AKT pathway in osteosarcoma cell [38]. miR-152-3p regulates TCF-4 pathway in OA rats to weaken chondrocyte apoptosis [39]. miR-152-3p overexpression suppressed angiotensin II-induced [40] and hypoxia-induced cardiomyocyte apoptosis in vitro [41].…”
Section: Declarationsmentioning
confidence: 99%
“…miR-152 attenuated lncRNA PVT1induced apoptosis via c-MET/PI3K/AKT pathway in osteosarcoma cell [38]. miR-152-3p regulates TCF-4 pathway in OA rats to weaken chondrocyte apoptosis [39]. miR-152-3p overexpression suppressed angiotensin II-induced [40] and hypoxia-induced cardiomyocyte apoptosis in vitro [41].…”
Section: Declarationsmentioning
confidence: 99%
“…Recent years, the anti-apoptotic effect of miR-152-3p in injury diseases have received increasing investment. miR-152-3p regulates TCF-4 pathway in OA rats to weaken chondrocyte apoptosis [31]. miR-152-3p overexpression suppressed angiotensin II-induced apoptosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer susceptibility 2 (CASC2) [ 56 ] and cancer susceptibility 19 (CASC19) [ 57 ] have been demonstrated to exhibit proinflammatory and proapoptotic effects by regulating IL-17 and the miR-152-3p/DDX6 axis, respectively. Furthermore, Zhang et al [ 58 ] found that the levels of ADP ribosylation factor related protein 1 (ARFRP1) and toll like receptor 4 (TLR4) were increased, whereas those of miR-15a-5p were decreased in lipopolysaccharide (LPS)-treated chondrocytes, and that ARFRP1 promoted the expression of inflammatory molecules, such as IL-6 and TNF-α, by regulating the NF-κB pathway.…”
Section: Regulatory Roles Of Lncrnas In Osteoarthritis Cartilagementioning
confidence: 99%